RFIC and MMIC design and technology - Robertson, I. D. (Ian D.); Lucyszyn, S. (Stepan) (Institution of Engineering and Technology, 2001)
The following topics are dealt with: devices and fabrication technology; passive components; CAD techniques; amplifiers; oscillators; mixers; switches and attenuators; phase shifters; integrated antennas; transceivers; and measurement techniques.